PENGARUH STRATEGI PEMASARAN DALAM PENJUALAN ONLINE DI CV. ADIARKO DIGITAL TEAM - Helmy Klau, Herlina; Risqi Amalia, Jian (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
At this time information technology has developed very rapidly, therefore many business people are using information technology systems to improve their digital technology-based businesses. This research aims to improve insight and work skills in the field of commercial electronic trading (e-commerce) or online. This type of research is descriptive research with an experimental approach. The data collection method used by researchers is to use observation and literature study. sales results in November amounted to 2609 products and December amounted to 3394 products, meaning that in December the company experienced an increase due to increased sales or consumer purchasing power rose at the end of the year. With the marketing strategy, it can be concluded that CV. Adiarko Digital Team has an effect on increasing sales results every month.